Antagonismo a Colletotrichum lindemuthianum e ativação de mecanismos de defesa em feijoeiro-comum desencadeados por Trichoderma spp - Stefanello, Vanessa Felix Vaz (2015)
The objective of the work was to evaluate the action of Trichoderma spp. and its filtered as biocontrol agent of anthracnose and resistance inducer in beans. Were conducted two experiments in vitro, where were made a germination test of Colletotrichum lindemuthianum conidium after the treatment with Trichoderma spp. filtered, and the direct confrontation test of 21 cultures isolated from Trichoderma spp. agains this pathogen were also conducted two experiments in vivo: on the first imposed treatments in base of Trichoderma in the beans inoculated via seed; on the second experiment the treatments aplication were made through foliar spray of filtered medium of Trichoderma spp. For the experiments in vivo were realized sheets collects for biochemical analysis, in which there were two collects for the experimente that were treated via seed (15 days after the foliar emergency and three days after the pathogen inoculation). Whereas for the experiment which the treatments were via foliar spray of filtered medium of Trichoderma, were realized three collectings, (the first without the treatment aplication, the second three days after the filtered pulverization and the third collect realized three days after the pathogen inoculation). Were determined the polyphenoloxidase activity (PFO), peroxidase (POX) and phenylalanine ammonia lyase (FAL), and were evaluated the total protein content, total phenols, lignin and the severity of anthracnose after treatments in base of Trichoderma for both experiments. For the germination test of C. lindemuthianum, conidium the filtered from the isolated TM1, TI1 and TOD1 reduced the germination in, 33%, 38% and 61% respectivily. In direct confrontation were realized that the isolated inhibited pathogen growth. For the PFO activity in via seed treatment, the isolated TLB12, TOD1 and TOD2B caused an increase thereof after challenge with the pathogen, while the treatment via foliar spray of Trichoderma filtered were not observed significant difference. The POX activity in beans treated at sowing, for the time 1 weren‟t observed difference between the treatments, whereas in the time 2 some isolated tended to suppress the enzymatic activity, while for plants treated via foliar pulverization notes the tendency to enzymatic suppression of POX in time 2 caused by some filtered in relation to the positive control. The FAL enzymatic activity and the total soluble protein contents both in the aplication of the treatments via seed and via foliar pulverization in beans didn‟t result in significant difference. For the total phenol contents and lignin the treatments in base of Trichoderma via sowing and via foliar pulverization didn‟t promote an icrease of the same in beans. The severity in treated beans presented in general low, making these inaccurate data